Efisiensi Ekonomis Usahatani Kelor Organik Di Moringa Organik Indonesia Blora Jawa - Hanisa Sismaya Lestari; Endah Lisarini1; Asep Saepul Alam; Rahmat Taufiq Dwi Jatmika (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2022)
Limitless study that conducted on moringa farming inversely to the benefits that have been felt by many people. Both as herbal medicine and as an alternative vegetable. The research has purpose to get know about the economical moringa used as community farming with examining the economic efficiency of moringa farming in Blora Regency precisely in Moringa Organic Indonesia Corp. Information and data were obtained from twenty respondents of Moringa farmers who have been cultivating Moringa for the last five to seven years. The data were analyzed using the Cobb Douglas production function approach and stochastic frontier analysis which will measure technical, allocative and economic efficiency. The results showed that: 1) Moringa farming in Blora has achieved technical efficiency. The average technical efficiency is 0.93. The lowest technical efficiency is 0.8 and the highest is 1.00; 2) The level of allocative efficiency of Moringa farming is on average 1.00 so that it is declared perfect efficiency; 3) Moringa farming in Blora achieves an economic efficiency of 0.93. It is hoped that the results of this study will provide information to the wider community that Moringa is one of the economic commodities that can be used as a source of income and can improve welfare in addition to meeting the nutritional needs of the community.